European economic integration and italien labour policies - Antonelli, Gilberto; De Liso, Nicola (Aldershot, 2004)
"For a long time now, the Italian economy and its labour market have been used as case studies due to the peculiarities they exhibit. This text is the result of a research project that has successfully analyzed how European economic integration has influenced Italy and particularly its labour market. The book highlights issues including labour policies and employment strategies, education, training and market trends."